2003
DOI: 10.2214/ajr.180.3.1800805
|View full text |Cite
|
Sign up to set email alerts
|

Using a Dedicated Lung-Marker System for Localization of Pulmonary Nodules Before Thoracoscopic Surgery

Abstract: The dedicated lung-marker system is a fast and effective method for localization of pulmonary nodules before thoracoscopic resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…Preoperative and intraoperative nodule localization techniques include computed tomography dye injection [15,16], intraoperative endoscopic ultrasonography [17] and preoperative computed tomography guided hookwire localization [18]. In our series, nodules as small as 4 mm in size were identified without the need of additional methods.…”
Section: Selected Controlled Ventilation Came With the Introduction Omentioning
confidence: 78%
“…Preoperative and intraoperative nodule localization techniques include computed tomography dye injection [15,16], intraoperative endoscopic ultrasonography [17] and preoperative computed tomography guided hookwire localization [18]. In our series, nodules as small as 4 mm in size were identified without the need of additional methods.…”
Section: Selected Controlled Ventilation Came With the Introduction Omentioning
confidence: 78%
“…Also, they reported that insertion of the hookwire does not negatively impact outcome for patients with malignancy, with no evidence of tumour seeding or dissemination secondary to hook insertion (27). The second commercially available hookwire system has a coiled tip to be placed within the lung parenchyma, with a flexible wire that is brought external and coiled on the chest wall prior to VATS (28). A number of groups have reported results using this system, with success rates ranging from 86-100% and dislodgement rates of 0-9% (28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…The second commercially available hookwire system has a coiled tip to be placed within the lung parenchyma, with a flexible wire that is brought external and coiled on the chest wall prior to VATS (28). A number of groups have reported results using this system, with success rates ranging from 86-100% and dislodgement rates of 0-9% (28)(29)(30)(31)(32). Other hookwire designs have been attempted, with success rates for VATS resection ranging from 88-100% with few complications reported and low rates of dislodgement (33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…It was recommended to place the wire or coil right into the solid nodule or more than 2 cm deep into the lung tissue for more stable anchorage (21). However, our experience demonstrated that this kind of manipulation might be unsuitable for GGN lesion, as it may dramatically increase the chance of dislodgment due to the comparatively soft and loose composition of these lesions.…”
Section: Discussionmentioning
confidence: 96%